Teachers' experiences and adaptations in navigating generational pedagogical shifts with digital native junior high students - Rulitawati; Salsabila Nurhaliza; Habibur Rachman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
The mismatch between traditional pedagogical approaches and digital-native learners' expectations poses substantial educational issues that need immediate attention. This research examined teachers' experiences with navigating generational pedagogical transitions while instructing digital-native students at junior high schools in Palembang. Participants, selected through purposive sampling, each had over 20 years of teaching experience and completed their education before the widespread integration of digital technology. Data collection utilized semi-structured interviews, non-participant classroom observations, and document analysis, analyzed through Colaizzi's phenomenological approach with triangulation for credibility. Findings revealed teachers' experiences evolved through five emotional stages from initial shock to eventual integration. Major challenges included technological competency gaps, infrastructure limitations, classroom management complexities, tensions between traditional and modern pedagogical values, and assessment difficulties. Teachers employed comprehensive adaptation strategies: segmented instruction with multimedia integration, strategic use of technology aligned with learning objectives, explicit digital citizenship instruction, continuous self-directed professional development, and cultivation of supportive learning environments. Results demonstrate that effectively managing generational pedagogical transitions requires comprehensive transformation beyond technical skills, necessitating systematic institutional support through infrastructure investment, continuous professional development, collaborative learning communities, adaptable curricula, and assessment reform to sustain teacher innovation in addressing digital-native learners. Key recommendations include establishing professional development programs, investing in digital infrastructure, creating teacher learning communities, developing flexible curricula, and implementing comprehensive support systems for teacher adaptation in the digital age.